Prevalence, prescriptions, outcomes and costs of type 2 diabetes patients with or without prior coronary artery disease or stroke: a longitudinal 5-year claims-data analysis of over 7 million inhabitants. (June 2021) - Maggioni, Aldo Pietro; Dondi, Letizia; Andreotti, Felicita; Ronconi, Giulia; Calabria, Silvia; Piccinni, Carlo; Pedrini, Antonella; Esposito, Imma; Martini, Nello
Aims: To analyze the prevalence, comorbidities, outcomes and costs of type 2 diabetes mellitus (T2DM) patients with and without coronary artery disease (CAD) or stroke in a population of over 7 million inhabitants. Methods: T2DM patients were identified in 2015 (accrual period) from the Ricerca e Salute (ReS) database linking administrative records to demographics. Based on 2013–2015 information, four cohorts were considered: #1 with CAD and/or stroke; #2 without CAD and/or stroke; #3 with chronic CAD but no myocardial infarction or stroke; #4 with chronic CAD undergoing percutaneous coronary interventions (PCI). Hospitalizations, drugs and other outpatient care were assessed from 2015 to 2017. Results: The prevalence of T2DM was 6% (441, 085/7, 365, 954). CAD and/or stroke in the previous 3 years affected 7.5% of T2DM patients (33, 153); this cohort was generally older, of male sex, with more comorbidities, prescriptions, and hospital admissions (50.5% versus 13.4% during the first follow-up year) compared to cohort #2. Yearly costs were over three-fold for cohort #1 versus #2, main drivers being hospitalizations in the former and drugs in the latter. Two-year cardiovascular events were recorded significantly more commonly in cohort #4 compared to the other cohorts. Guideline-recommended lipid-lowering therapy was <80% in all but cohort #4. Conclusions: The present analysis points to three areas of potential improvement in T2DM management: (a) guideline-recommended treatment patterns of T2DM patients; (b) three-fold recurrences and costs in T2DM patients with, compared to those without, prior cardiovascular events; (c) high event rates associated with chronic CAD and PCI, warranting specific studies aimed at improved prevention.